Nitrogen and irrigation water management in corn (Zea mays) under no-tillage and conventional tillage systems - Ziaeyan, Abdolhossein; Mousavi, Seyed Majid; Karami, Alidad; Ziaeian, Mohammad (The Indian Journal of Agricultural Sciences, 2020)
Organic carbon and irrigation water scarcity are two major limiting factors in corn (Zea mays L.) production of Fars province which is located in the south of Iran. Soil tillage systems can affect the nitrogen and water utilization. In 2015-2017, by using the strip-split plot design and two line-source sprinkler irrigation systems, effects of 0, 90, 180, and 270 kg.ha-1 of pure nitrogen and 6400, 7500, 8550, and 9600 m3.ha-1 of irrigation water in conventional, and no-tillage systems were investigated. Results showed that conventional tillage system had high WUE and foliage yield than no-tillage systems. Based on the obtained results, in the terms of dry foliage yield, combined application of 8550 m3.ha-1 irrigation water and 90 kg N.ha-1 (I2N90 treatment) are introduced as the superior treatments in both of two tillage systems. While, in terms of WUE, combined application of 8550 m3.ha-1 irrigation water and 90 kg N.ha-1 (I2N90 treatment) in conventional tillage and combined application of 7500 m3.ha-1 irrigation water and 135 kg N.ha-1 (I3N135 treatment) in no-tillage systems are introduced as the superior treatments.